Understanding Chinese and Western development finance in Uganda, South Africa, and Zimbabwe - Edwin Muchapondwa; Samson Mukanjari (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
China's importance as a major donor outside the traditional Western donors has been increasing and this has helped to bridge the funding gaps in developing countries. At the same time, South-South financial assistance still comes with less conditionality making China's aid model different to Western donors. China dominates as a donor for Zimbabwe with substantial aid also going into Uganda and South Africa while South Africa is the darling of Western donors. Chinese funded projects are not confined to a specific sector and the scale of the projects varies across countries. While little is known about environmental aid from China, the magnitude of environmental aid from Western donors suggests there is a need to explore other areas to leverage the effect of environmental aid on the environment. Overall we find that aid disbursements are significantly lower than commitments for all three countries .
Keywords: O19; Q56; 330; Africa; aid; China; development finance; environmental aid; South-South co-operation